Egypt : land of the pharaohs - Time-Life Books (Alexandria, Va. : Time-Life Books, 1992)
Examines discoveries of ancient Egypt, including mummies, tombs, pyramids, and treasures.
Contents: Mummies, tombs, and treasures (p.9) -- Essay : Home of the giants (p.34) -- In the shadow of the pyramids (p.45) -- Essay : Houses of eternity (p.73) -- The pharaoh whom history could not forget (p.81) -- Essay : The stories mummies tell (p.105) -- In the valley of death (p.117) -- Essay : The personal Tutankhamen (p.149) -- Timeline (p.158) -- Acknowledgments (p.160) --- Picture credits (p.160) -- Bibliography (p.162) -- Index (p.164).
Includes bibliographical references (p. 162-164) and index.
Keywords: Egypt -- Antiquities; Excavations (Archaeology) -- Egypt; Egypt -- Civilization -- To 332 B.C.; Arqueologia -- Egito antigo; z; 2; Egypt -- Civilization -- To 332 B.C.